2001
DOI: 10.1034/j.1399-6576.2001.045005634.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation assessment in healthy pigs undergoing single xenon anaesthesia and combinations with isoflurane and sevoflurane

Abstract: In our study, xenon monoanaesthesia and combinations of xenon with isoflurane and sevoflurane did not lead to pathologic alterations in the measured coagulation parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
(29 reference statements)
1
7
0
1
Order By: Relevance
“…In addition to a lack of neurotoxic profile [30], prolonged xenon exposure in the critical care setting was not associated with any deterioration in haematological and biochemical variables [3]. These data are consistent with previous reports suggesting that xenon exerts no effect on coagulation [51] or platelet function in vitro [52], nor any effect on the immune system [53]. Xenon does not impair hepatic or renal function [3,54].…”
Section: Organ Effects and Toxicitysupporting
confidence: 93%
“…In addition to a lack of neurotoxic profile [30], prolonged xenon exposure in the critical care setting was not associated with any deterioration in haematological and biochemical variables [3]. These data are consistent with previous reports suggesting that xenon exerts no effect on coagulation [51] or platelet function in vitro [52], nor any effect on the immune system [53]. Xenon does not impair hepatic or renal function [3,54].…”
Section: Organ Effects and Toxicitysupporting
confidence: 93%
“…The specific inhibition of the NMDA receptor may explain the attractive pharmacological properties of Xe in the context of anesthesia (2–5). Furthermore, in a recent study, Wilhelm et al observed in an in vivo brain injury model in rats and in vitro a neuroprotective effect of Xe (7).…”
Section: Discussionmentioning
confidence: 99%
“…X enon (Xe) is a specific antagonist of the NMDA (N‐methyl‐D‐aspartate)‐type glutamate receptor (1) and has been shown to be a very effective and safe anesthetic agent in numerous studies (2–5). Recent investigations were able to demonstrate that Xe is unique amongst anesthetics with known NMDA receptor antagonist action because Xe exhibits neuroprotective properties without coexisting neurotoxicity (6).…”
mentioning
confidence: 99%
“…19,20 Estes resultados também são consistentes com estudos prévios que não identificaram in vitro interferência na coagulação 63 ou na função plaquetária. 64 Também dados de estudos experimentais in vitro, sugerem que o xénon não perturba o sistema imunitário humano, preservando a capacidade anti--bacteriana dos neutrófilos e monócitos e a capacidade de produção de citocinas inflamatórias dos monócitos.…”
Section: Outros Sistemasunclassified